^{1}

^{*}

^{2}

^{3}

^{3}

In this paper, we suggest and analyze a modified Thakur three-step iterative algorithm to approximate a common element of the set of common fixed points of Garcia-Falset mappings and the set of solutions of some variational inequalities in Banach spaces. We also establish strong convergence theorems for a common solution of the above-said problems by the proposed iterative algorithm without the compactness assumption. The methods in this paper are novel and different from those given in many other papers. And the results are the extension and improvement of the recent results announced by many others.

In the early 1960s, Stampacchia [

On the other hand, the theory of fixed points has become one of the very powerful tools of nonlinear analysis. Further, by the development of accurate and efficient techniques for computing fixed points, the effectiveness of the concept for applications has been increased enormously. In recent years, the theory of fixed points has grown rapidly into a flourishing and dynamic field of study both in pure and applied mathematics. It has become one of the most essential tools in the study of nonlinear phenomena. The iterative methods for approximating fixed points are of great importance for modern numerical mathematics (see, e.g., [

The study for variational inequalities, fixed points and approximation algorithms became a topic of intensive research efforts in recent years. Nowadays, this is still one of the most active fields in mathematics. Meanwhile, the nature of many practical problems arouses an iterative approach to the solution. Recently, Garcia-Falset et al. [

Motivated and inspired by the work in the literature, we suggest and analyze a modified Thakur three-step iterative algorithm to approximate a common element of the set of common fixed points of Garcia-Falset mappings and the set of solutions of some variational inequalities in Banach spaces. We also establish strong convergence theorems for a common solution of the above-said problems by the proposed iterative algorithm without the compactness assumption. The methods in this paper are novel and different from those given in many other papers. And the results are the extension and improvement of the recent results in the literature; see [

Throughout this paper, we assume that E is a real Banach space with a dual E * , ℝ is the set of real numbers, 〈 ⋅ , ⋅ 〉 is the generalized duality pairing between E and E * , I is the identity mapping on E, and ℕ is the set of nonnegative integers. We denote by x n → x and x n ⇀ x the strong and weak convergence of the sequence { x n } , respectively. And ω w ( x n ) denote the set of weak limit points of the sequence { x n } . The set of fixed points of T : C → C is denoted by Fix ( T ) . The (normalized) duality mapping of E is denoted by J, that is,

J ( x ) = { x * ∈ E * : 〈 x , x * 〉 = ‖ x ‖ 2 , ‖ x * ‖ = ‖ x ‖ }

for all x ∈ E . If E is a Hilbert space, then J = I , where I is the identity mapping.

A Banach space E is said to be smooth if the limit

l i m t → 0 ‖ x + t y ‖ − ‖ x ‖ t

exists for all x , y on the unit sphere S ( E ) = { x ∈ E : ‖ x ‖ = 1 } .

Assume φ defined ℝ + : = [ 0 , ∞ ) is a continuous strictly increasing function such that φ ( 0 ) = 0 and lim r → ∞ φ ( r ) = ∞ . This function φ is called a gauge function. The duality mapping J φ : E → 2 E * defined by

J φ ( x ) = { x * ∈ E * : 〈 x , x * 〉 = ‖ x ‖ φ ( ‖ x ‖ ) and ‖ x * ‖ = φ ( ‖ x ‖ ) } .

In the case that φ ( t ) = t , J φ = J , where J is the normalized duality mapping. Clearly, the relation J φ ( x ) = φ ( ‖ x ‖ ) ‖ x ‖ J ( x ) , ∀ x ≠ 0 holds (see, e.g., [

Φ ( t ) = ∫ 0 t φ ( r ) d r .

As we know that J φ ( x ) is the subdifferential of the convex function Φ ( ‖ ⋅ ‖ ) at x. Following Browder [^{*} topology. Every l p ( 1 < p < ∞ ) space has a weakly continuous duality map with the gauge φ ( t ) = t p − 1 (see, e.g., [

Remark 2.1. It is well known that J φ is single-valued if and only if ( E , ‖ ⋅ ‖ ) is smooth (see, e.g., [

Let E be a real Banach space, C a nonempty closed convex subset of E , T a mapping on C and F ( T ) : = { x ∈ C : T x = x } .

Definition 2.1. A mapping T : C → C is said to be:

1) Contractive if there exists a constant α ∈ ( 0,1 ) such that

‖ T x − T y ‖ ≤ α ‖ x − y ‖ , ∀ x , y ∈ C ;

2) Nonexpansive if ‖ T x − T y ‖ ≤ ‖ x − y ‖ for all x , y ∈ C .

3) Quasinonexpansive if ‖ T x − x * ‖ ≤ ‖ x − x * ‖ , ∀ x ∈ C , x * ∈ F ( T ) .

Definition 2.2. A mapping T : C → E is said to satisfy condition (C) on C if for all x , y ∈ C with ‖ T x − x ‖ ≤ 2 ‖ x − y ‖ , one has that ‖ T x − T y ‖ ≤ ‖ x − y ‖ .

Recently, Garcia-Falset et al. [

Definition 2.3. Let C be a nonempty subset of a Banach space E and μ ≥ 1 . A mapping T : C → E which satisfies the inequality

‖ x − T y ‖ ≤ μ ‖ x − T x ‖ + ‖ x − y ‖ , ∀ x , y ∈ C ;

is said to be endowed with ( E μ )-property. Moreover,we say that T satisfies condition (E)on C,whenever T satisfies condition ( E μ ),for some μ ≥ 1 .

Clearly, condition (E) is weaker than condition (C).

Lemma 2.4. [

Recall that, if C and D are nonempty subsets of a Banach space E such that C is closed convex and D ⊂ C , then a mapping Q : C → D is sunny [

P ( x + t ( x − P ( x ) ) ) = P ( x )

for all x ∈ C and t ≥ 0 , whenever P x + t ( x − P ( x ) ) ∈ C . A mapping P : C → D is called a retraction if P x = x for all x ∈ D . Furthermore, P is a sunny nonexpansive retraction from C onto D if P is retraction from C onto D which is also sunny and nonexpansive. A subset D of C is called a sunny nonexpansive retraction of C if there exists a sunny nonexpansive retraction from C onto D. The following lemma collects some properties of the sunny nonexpansive retraction.

Lemma 2.5. [

1) P is sunny and nonexpansive;

2) ‖ P x − P y ‖ 2 ≤ 〈 x − y , j ( P x − P y ) 〉 , ∀ x , y ∈ C ;

3) 〈 x − P x , j ( y − P x ) 〉 ≤ 0, ∀ x ∈ C , y ∈ D .

Lemma 2.6. [

‖ ∑ n = 1 N λ n x n ‖ 2 ≤ ∑ n = 1 N λ n ‖ x ‖ 2 − λ i λ j g ( ‖ x i − x j ‖ ) .

Lemma 2.7. [

s n + 1 ≤ ( 1 − α n ) s n + α n γ n + β n , n ∈ ℕ .

Then, lim n → ∞ s n = 0 .

Lemma 2.8. [

τ ( n ) : = max { k ≤ n : w n k < w n k + 1 }

for all n ≥ n 0 (for some n 0 large enough). Then { τ ( n ) } is a nondecreasing sequence such that lim n → ∞ τ ( n ) = ∞ and it holds that

max { w τ ( n ) , w n } ≤ w τ ( n ) + 1 .

Theorem 3.1. Let C be a nonempty closed convex subset of a uniformly convex and smooth Banach space E which admits a weakly continuous duality mapping J. Let f : C → C be a contractive mapping with constant r ∈ ( 0,1 ) , T : C → C be a mapping satisfying condition (E) with Fix ( T ) ≠ ∅ . For arbitrarily given x 0 ∈ C , let { x n } be the sequence generated iteratively by:

{ z n = ( 1 − γ n ) x n + γ n T x n , y n = ( 1 − β n ) x n + β n T x n , x n + 1 = α n f x n + δ n T z n + η n T y n , ∀ n ∈ ℕ , (3.1)

where { α n } , { β n } , { γ n } , { δ n } and { η n } are real number sequences in [0, 1] satisfying:

1) lim n → ∞ α n = 0 and ∑ n = 1 ∞ α n = ∞ ,

2) α n + δ n + η n = 1 ,

3) 0 < lim inf n → ∞ δ n ≤ lim sup n → ∞ δ n < 1 , 0 < lim inf n → ∞ γ n ≤ lim sup n → ∞ γ n < 1 and 0 < lim inf n → ∞ η n ≤ lim sup n → ∞ η n < 1 .

Then the sequence { x n } converges strongly to a point p ∈ Fix ( T ) ,which is also the unique solution of the hierarchical variational inequality

〈 f ( p ) − p , j ( q − p ) 〉 ≤ 0, ∀ q ∈ Fix ( T ) .

In other words,p is the unique fixed point of the mapping P Fix ( T ) f ,that is, p = P Fix ( T ) f ( p ) .

Proof. We divide the proof into two steps.

Step 1. Firstly, we prove that the sequence { x n } is bounded. Taking x * ∈ Fix ( T ) arbitrarily, it follows by Definition 2.3 that T is quasi-nonexpansive. Hence, we get from (3.1) that

‖ y n − x * ‖ = ‖ ( 1 − β n ) x n + β n T x n − x * ‖ ≤ ( 1 − β n ) ‖ x n − x * ‖ + β n ‖ T x n − x * ‖ ≤ ( 1 − β n ) ‖ x n − x * ‖ + β n ‖ x n − x * ‖ ≤ ‖ x n − x * ‖ . (3.2)

In the same way, we get that

‖ z n − x * ‖ = ‖ ( 1 − γ n ) x n + γ n T x n ‖ ≤ ( 1 − γ n ) ‖ x n − x * ‖ + γ n ‖ T x n − x * ‖ ≤ ( 1 − γ n ) ‖ x n − x * ‖ + γ n ‖ x n − x * ‖ ≤ ‖ x n − x * ‖ . (3.3)

It follows from (3.1), (3.2) and (3.3) that

‖ x n + 1 − x * ‖ = ‖ α n f x n + δ n T z n + η n T y n − x * ‖ ≤ α n ‖ f x n − x * ‖ + δ n ‖ T z n − x * ‖ + η n ‖ T y n − x * ‖ ≤ α n ‖ f x n − f ( x * ) ‖ + α n ‖ f ( x * ) − x * ‖ + δ n ‖ T z n − x * ‖ + η n ‖ T y n − x * ‖ ≤ α n r ‖ x n − x * ‖ + α n ‖ f ( x * ) − x * ‖ + δ n ‖ z n − x * ‖ + η n ‖ y n − x * ‖

≤ α n r ‖ x n − x * ‖ + α n ‖ f ( x * ) − x * ‖ + δ n ‖ x n − x * ‖ + η n ‖ x n − x * ‖ = α n ‖ f ( x * ) − x * ‖ + ( 1 − ( 1 − r ) α n ) ‖ x n − x * ‖ ≤ max { ‖ f ( x * ) − x * ‖ 1 − r , ‖ x 0 − x * ‖ } .

This implies that the sequence { x n } is bounded, so are { y n } and { z n } .

Step 2. We show that lim n → ∞ ‖ x n − p ‖ = 0 . Here again p ∈ Fix ( T ) , which is also the unique solution of the hierarchical variational inequality

〈 f ( p ) − p , q − p 〉 ≤ 0, ∀ q ∈ Fix ( T ) .

We analyze this step by considering the following two cases.

Case A: Put Γ n = ‖ x n − p ‖ for all n ∈ ℕ and assume that Γ n + 1 ≤ Γ n for all n ≥ n 0 (for n 0 large enough). In this case, it is easily seen that the lim n → ∞ Γ n exists. Now we prove that

l i m n → ∞ ‖ T x n − x n ‖ = 0.

To see this, we apply Lemma 2.6 to (3.1) to get

‖ x n + 1 − p ‖ 2 = ‖ α n f x n + δ n T z n + η n T y n − p ‖ 2 ≤ α n ‖ f x n − p ‖ 2 + δ n ‖ T z n − p ‖ 2 + η n ‖ T y n − p ‖ 2 ≤ α n ‖ f x n − p ‖ 2 + δ n ‖ z n − p ‖ 2 + η n ‖ y n − p ‖ 2 ≤ α n ‖ f x n − p ‖ 2 + η n ‖ x n − p ‖ 2 + δ n ‖ x n − p ‖ 2 − δ n γ n ( 1 − γ n ) g ( ‖ T x n − x n ‖ ) ≤ α n ‖ f x n − p ‖ 2 + ( 1 − α n ) ‖ x n − p ‖ 2 − δ n γ n ( 1 − γ n ) g ( ‖ T x n − x n ‖ ) , (3.4)

which is reduced to the inequality

δ n γ n ( 1 − γ n ) g ( ‖ T x n − x n ‖ ) ≤ α n ( ‖ f x n − p ‖ 2 − ‖ x n − p ‖ 2 ) + ( Γ n 2 − Γ n + 1 2 ) .

Then, by using the conditions (1)-(3) and the assumption Γ n + 1 ≤ Γ n , we derive that

l i m n → ∞ g ( ‖ T x n − x n ‖ ) = 0. (3.5)

It follows from the property of g that

lim n → ∞ ‖ T x n − x n ‖ = 0. (3.6)

Repeat the argument for (3.4) to obtain

‖ x n + 1 − p ‖ 2 = ‖ α n ( f x n − p ) + δ n ( T z n − p ) + η n ( T y n − p ) ‖ 2 ≤ α n ‖ f x n − p ‖ 2 + δ n ‖ T z n − p ‖ 2 + η n ‖ T y n − p ‖ 2 − δ n η n g ( ‖ T y n − T z n ‖ ) ≤ α n ‖ f x n − p ‖ 2 + δ n ‖ x n − p ‖ 2 + η n ‖ x n − p ‖ 2 − δ n η n g ( ‖ T y n − T z n ‖ ) = α n ‖ f x n − p ‖ 2 + ( 1 − α n ) ‖ x n − p ‖ 2 − δ n η n g ( ‖ T y n − T z n ‖ ) , (3.7)

which implies that

δ n η n g ( ‖ T y n − T z n ‖ ) ≤ α n ( ‖ f x n − p ‖ 2 − ‖ x n − p ‖ 2 ) + ( Γ n 2 − Γ n + 1 2 ) . (3.8)

Hence, by using the conditions (1)-(3), the assumption Γ n + 1 ≤ Γ n and the property of g, we derive that

lim n → ∞ ‖ T y n − T z n ‖ = 0. (3.9)

Write

x n + 1 − T y n = α n ( f x n − T y n ) + δ n ( T z n − T y n )

and apply the condition (1) and (3.9) to get

lim n → ∞ ‖ x n + 1 − T y n ‖ = 0. (3.10)

Note that

‖ x n + 1 − x n ‖ ≤ ‖ x n + 1 − T y n ‖ + ‖ T y n − x n ‖ ≤ ‖ x n + 1 − T y n ‖ + μ ‖ x n − T x n ‖ + ‖ x n − y n ‖ ≤ ‖ x n + 1 − T y n ‖ + μ ‖ x n − T x n ‖ + β n ‖ x n − T x n ‖ . (3.11)

Apply the condition (1), (3.6) and (3.10) to get

lim n → ∞ ‖ x n + 1 − x n ‖ = 0. (3.12)

Since { x n } is bounded, there exists a subsequence { x n k } of { x n } such that x n k converges weakly to a point q and moreover

lim sup n → ∞ 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 = l i m k → ∞ 〈 f ( p ) − p , j ( x n k + 1 − p ) 〉 . (3.13)

Apply (3.6), (3.12) and Lemma 2.4 to infer that x n k + 1 converges weakly to a point q and q ∈ Fix ( T ) . This together with the property of the sunny nonexpansive retraction implies

lim sup n → ∞ 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 = l i m k → ∞ 〈 f ( p ) − p , j ( x n k + 1 − p ) 〉 = l i m k → ∞ 〈 f ( p ) − p , j ( q − p ) 〉 = 〈 f ( p ) − P F ( T ) p , j ( q − P F ( T ) p ) 〉 ≤ 0.

Finally, we prove that lim n → ∞ ‖ x n − p ‖ = 0 . Using (3.1) and the assumption Γ n + 1 ≤ Γ n , we have that, for all n ≥ n 0 ,

‖ x n + 1 − p ‖ 2 = α n 〈 f x n − p , j ( x n + 1 − p ) 〉 + δ n 〈 T z n − p , j ( x n + 1 − p ) 〉 + η n 〈 T y n − p , j ( x n + 1 − p ) 〉 ≤ α n 〈 f x n − f ( p ) , j ( x n + 1 − p ) 〉 + α n 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 + δ n 〈 T z n − p , j ( x n + 1 − p ) 〉 + η n 〈 T y n − p , j ( x n + 1 − p ) 〉

≤ α n r ‖ x n − p ‖ ‖ x n + 1 − p ‖ + α n 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 + δ n ‖ T z n − p ‖ ‖ x n + 1 − p ‖ + η n ‖ T y n − p ‖ ‖ x n + 1 − p ‖ ≤ α n r ‖ x n − p ‖ ‖ x n + 1 − p ‖ + α n 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 + δ n ‖ z n − p ‖ ‖ x n + 1 − p ‖ + η n ‖ y n − p ‖ ‖ x n + 1 − p ‖

≤ α n r ‖ x n − p ‖ ‖ x n + 1 − p ‖ + α n 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 + δ n ‖ x n − p ‖ ‖ x n + 1 − p ‖ + η n ‖ x n − p ‖ ‖ x n + 1 − p ‖ ≤ ( 1 − α n ( 1 − r ) ) ‖ x n − p ‖ ‖ x n + 1 − p ‖ + α n 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 ≤ ( 1 − α n ( 1 − r ) ) ‖ x n − p ‖ 2 + α n 〈 f ( p ) − p , j ( x n + 1 − p ) 〉 .

By virtue of (3.13) and Lemma 2.7 and noticing (3.14), we get

lim n → ∞ ‖ x n − p ‖ = 0.

Case B. Assume that { Γ n } is nondecreasing. From Lemma 2.8, there exists a nondecreasing sequence { τ ( n ) } ⊂ ℕ such that

max { Γ τ ( n ) , Γ n } ≤ Γ τ ( n ) + 1 . (3.14)

Following an argument similar to that in Case A and noticing (3.14), we derive that

l i m n → ∞ ‖ T x τ ( n ) + 1 − x τ ( n ) ‖ = 0 (3.15)

and

l i m n → ∞ ‖ x τ ( n ) + 1 − x τ ( n ) ‖ = 0. (3.16)

Repeat the argument for (3.13) to obtain

lim sup n → ∞ 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 ≤ 0. (3.17)

Finally, we show that lim n → ∞ Γ τ ( n ) = 0 . It follows (3.1) and (3.17) that

‖ x τ ( n ) + 1 − p ‖ 2 = α n 〈 f x τ ( n ) − p , j ( x τ ( n ) + 1 − p ) 〉 + δ τ ( n ) 〈 T z τ ( n ) − p , j ( x τ ( n ) + 1 − p ) 〉 + η τ ( n ) 〈 T y τ ( n ) − p , j ( x τ ( n ) + 1 − p ) 〉 ≤ α τ ( n ) 〈 f x τ ( n ) − f ( p ) , j ( x τ ( n ) + 1 − p ) 〉 + α τ ( n ) 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 + δ τ ( n ) 〈 T z τ ( n ) − p , j ( x τ ( n ) + 1 − p ) 〉 + η τ ( n ) 〈 T y τ ( n ) − p , j ( x τ ( n ) + 1 − p ) 〉

≤ α τ ( n ) r ‖ x τ ( n ) − p ‖ ‖ x τ ( n ) + 1 − p ‖ + α τ ( n ) 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 + δ τ ( n ) ‖ T z τ ( n ) − p ‖ ‖ x τ ( n ) + 1 − p ‖ + η τ ( n ) ‖ T y τ ( n ) − p ‖ ‖ x τ ( n ) + 1 − p ‖ ≤ α τ ( n ) r ‖ x τ ( n ) − p ‖ ‖ x n + 1 − p ‖ + α τ ( n ) 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 + δ τ ( n ) ‖ z τ ( n ) − p ‖ ‖ x n + 1 − p ‖ + η τ ( n ) ‖ y τ ( n ) − p ‖ ‖ x n + 1 − p ‖

≤ α τ ( n ) r ‖ x τ ( n ) − p ‖ ‖ x n + 1 − p ‖ + α τ ( n ) 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 + δ τ ( n ) ‖ x τ ( n ) − p ‖ ‖ x n + 1 − p ‖ + η τ ( n ) ‖ x τ ( n ) − p ‖ ‖ x n + 1 − p ‖ ≤ ( 1 − α τ ( n ) ( 1 − r ) ) ‖ x τ ( n ) − p ‖ ‖ x n + 1 − p ‖ + α τ ( n ) 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 ≤ ( 1 − α n ( 1 − r ) ) ‖ x τ ( n ) + 1 − p ‖ 2 + α n 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 . (3.18)

After simplifying, we have

( 1 − r ) ‖ x τ ( n ) + 1 − p ‖ 2 ≤ 〈 f ( p ) − p , j ( x τ ( n ) + 1 − p ) 〉 .

This together with the (3.17) implies that

l i m n → ∞ ‖ x τ ( n ) + 1 − p ‖ = 0,

Further, Lemma 2.8 implies

l i m n → ∞ ‖ x n − p ‖ ≤ l i m n → ∞ ‖ x τ ( n ) + 1 − p ‖ = 0,

that is, x n → p as n → ∞ . This completes the proof.

Remark 3.2. The main results in this paper extend and generalize corresponding results in [

1) The subset C of Banach space E does not have to be compact in our Theorem 3.1. However,this assumption is very necessary in Theorem 3.4 of Usurelu et al. [

2)Our result is new and the proofs are simple and different from those in [

From Theorem 3.1, we deduce immediately the following results

Corollary 4.1. Let C be a nonempty closed convex subset of a uniformly convex and smooth Banach space E which admits a weakly continuous duality mapping J, f : C → C be a contractive mapping with constant r ∈ ( 0,1 ) , T : C → C be a nonexpansive mapping with Fix ( T ) ≠ ∅ . For arbitrarily given x 0 ∈ C , let { x n } be the sequence generated iteratively by:

{ z n = ( 1 − γ n ) x n + γ n T x n , y n = ( 1 − β n ) x n + β n T x n , x n + 1 = α n f x n + δ n T z n + η n T y n , ∀ n ∈ ℕ , (4.1)

where { α n } , { β n } , { γ n } , { δ n } and { η n } are real number sequences in [0, 1] satisfying:

1) lim n → ∞ α n = 0 and ∑ n = 1 ∞ α n = ∞ ,

2) α n + δ n + η n = 1 ,

3) 0 < lim inf n → ∞ δ n ≤ lim sup n → ∞ δ n < 1 , 0 < lim inf n → ∞ γ n ≤ lim sup n → ∞ γ n < 1 and 0 < lim inf n → ∞ η n ≤ lim sup n → ∞ η n < 1 .

Then the sequence { x n } converges strongly to a point p ∈ Fix ( T ) , which is also the unique solution of the hierarchical variational inequality

〈 f ( p ) − p , j ( q − p ) 〉 ≤ 0, ∀ q ∈ Fix ( T ) .

In other words, p is the unique fixed point of the mapping P Fix ( T ) f , that is, p = P Fix ( T ) f ( p ) .

Corollary 4.2. Let C be a nonempty closed convex subset of a uniformly convex and smooth Banach space E which admits a weakly continuous duality mapping J. Let T : C → C be a nonexpansive mapping with Fix ( T ) ≠ ∅ . For arbitrarily given x 0 , u ∈ C , let { x n } be the sequence generated iteratively by:

{ z n = ( 1 − γ n ) x n + γ n T x n , y n = ( 1 − β n ) x n + β n T x n , x n + 1 = α n u + δ n T z n + η n T y n , ∀ n ∈ ℕ , (4.2)

where { α n } , { β n } , { γ n } , { δ n } and { η n } are real number sequences in [0, 1] satisfying:

1) lim n → ∞ α n = 0 and ∑ n = 1 ∞ α n = ∞ ,

2) α n + δ n + η n = 1 ,

3) 0 < lim inf n → ∞ δ n ≤ lim sup n → ∞ δ n < 1 , 0 < lim inf n → ∞ γ n ≤ lim sup n → ∞ γ n < 1 and 0 < lim inf n → ∞ η n ≤ lim sup n → ∞ η n < 1 .

Then the sequence { x n } converges strongly to a point p ∈ Fix ( T ) ,which is also the unique solution of the hierarchical variational inequality

〈 u − p , j ( q − p ) 〉 ≤ 0, ∀ q ∈ Fix ( T ) .

In other words,p is the unique fixed point of the mapping P Fix ( T ) u ,that is, p = P Fix ( T ) u .

Corollary 4.3. Let C be a nonempty closed convex subset of a Hilbert space H, f : C → C be a contractive mapping with constant r ∈ ( 0,1 ) , T : C → C be a nonexpansive mapping with Fix ( T ) ≠ ∅ . For arbitrarily given x 0 ∈ C , let { x n } be the sequence generated iteratively by:

{ z n = ( 1 − γ n ) x n + γ n T x n , y n = ( 1 − β n ) x n + β n T x n , x n + 1 = α n f x n + δ n T z n + η n T y n , ∀ n ∈ ℕ , (4.3)

1) lim n → ∞ α n = 0 and ∑ n = 1 ∞ α n = ∞ ,

2) α n + δ n + η n = 1 ,

Then the sequence { x n } converges strongly to a point p ∈ Fix ( T ) ,which is also the unique solution of the hierarchical variational inequality

〈 f ( p ) − p , q − p 〉 ≤ 0, ∀ q ∈ Fix ( T ) .

In other words,p is the unique fixed point of the mapping P Fix ( T ) f ,that is, p = P Fix ( T ) f ( p ) .

The present work has been aimed to theoretically establish a new iterative scheme for finding a common element of the set of common fixed points of generalized nonexpansive mappings enriched with property (E) and the set of solutions of some variational inequalities in Banach spaces without the compactness assumption. Our results can be viewed as improvement, supplementation, development and extension of the corresponding results in some references to a great extent.

This research was supported by the Key Scientific Research Projects of Higher Education Institutions in Henan Province (20A110038).

The authors declare no conflicts of interest regarding the publication of this paper.

Chen, X.H., Han, W.X., Gong, L.P. and Luo, C.J. (2020) A Modified Thakur Three-Step Iterative Algorithm to Garcia-Falset Mappings and Variational Inequalities. Journal of Applied Mathematics and Physics, 8, 2930-2942. https://doi.org/10.4236/jamp.2020.812216